Souza, E. (2013). Catábases: estudos sobre as viagens aos infernos na antiguidade. São Paulo. Annablume Clássica. - Serra, Ordep José Trindade (Revista Archai, 2015)
SOUZA, E. (2013). Catábases: estudos sobre as viagens aos infernos na antiguidade. São Paulo. Annablume Clássica.